2021
DOI: 10.7759/cureus.19469
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lockdown and Unlock Following COVID-19 on the Presentation of Patients With Endophthalmitis at a Tertiary Eye Center Over One Year

Abstract: Introduction Endophthalmitis is an emergency where patients need immediate intervention to salvage both vision and the globe. Regular follow-up care and close monitoring of the status of the patient are crucial in determining the final outcomes of the treatment. While there is ample literature on the epidemiology and demography of endophthalmitis across the globe, no information exists on the effect of the coronavirus disease 2019 (COVID-19) pandemic on the presentation patterns of endophthalmitis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…This would theoretically lead to a heightened probability of the development of endogenous endophthalmitis. Das et al,14 indeed reported an increased frequency of endogenous cases in their institution, along with a decreased rate of posttraumatic. Additional risk factors for the development of endophthalmitis could be advanced age, concomitant health problems, such as diabetes mellitus, congenital immunodeficiencies, sepsis, tuberculosis, HIV, hepatitis, urinary infections, skin infections, keratitis, indwelling catheters, intravenous drug abuse, and the prolonged use of antibiotics, CS and immunomodulators 1,2,4,[7][8][9].…”
mentioning
confidence: 84%
See 3 more Smart Citations
“…This would theoretically lead to a heightened probability of the development of endogenous endophthalmitis. Das et al,14 indeed reported an increased frequency of endogenous cases in their institution, along with a decreased rate of posttraumatic. Additional risk factors for the development of endophthalmitis could be advanced age, concomitant health problems, such as diabetes mellitus, congenital immunodeficiencies, sepsis, tuberculosis, HIV, hepatitis, urinary infections, skin infections, keratitis, indwelling catheters, intravenous drug abuse, and the prolonged use of antibiotics, CS and immunomodulators 1,2,4,[7][8][9].…”
mentioning
confidence: 84%
“…20 Some of their cases were associated with oral commensals, an unusual cause of post vitrectomy endophthalmitis. 20 Endogenous cases, on the other hand, have been on the rise 14 , especially those caused by fungal pathogens. Schroff et al, 21 reported on 5 eyes with endophthalmitis in 7 patients with severe COVID-19 pneumonia and long-term CS therapy (80-180 days).…”
Section: Endophthalmitis and Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…The All India Ophthalmology Society published the preferred practice guidelines for glaucoma diseases that outlined triaging patients into high risk, medium risk and low risk based on the complaints and nature of the disease, provided guidelines on intraocular pressure measurement techniques and laid down protocols related to gonioscopy evaluation, investigations, lasers and surgical procedures (7). Studies from India have helped to identify the vulnerable patients such as females, pediatric age group, elderly population and rural geography who have not been able to access eyecare services (8)(9)(10)(11)(12)(13). In this new normal we need to understand the trends of patients with chronic diseases such as glaucoma that warrants close monitoring and follow-up care.…”
Section: Introductionmentioning
confidence: 99%